2005
DOI: 10.1073/pnas.0501956102
|View full text |Cite
|
Sign up to set email alerts
|

Long-term potentiation of exogenous glutamate responses at single dendritic spines

Abstract: Long-term increases in the strength of excitatory transmission at Schaffer collateral-CA1 cell synapses of the hippocampus require the insertion of new ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionate receptors (AMPARs) into the synapse, but the kinetics of this process are not well established. Using microphotolysis of caged glutamate to activate receptors at single dendritic spines in hippocampal CA1 cells, we report the long-lasting potentiation of AMPAR-mediated currents with only a single pairing of photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
128
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(143 citation statements)
references
References 42 publications
14
128
1
Order By: Relevance
“…It is possible that translocation of perisynaptic AMPARs and subunit switch occur very rapidly with pairing protocol and that these processes were already completed by the time PhTx433 was added (20). This scenario is consistent with more GluR2-containing AMPARs being present after LTP induction (42). An alternative scenario is that different induction protocols leads to two different forms of LTP, one that requires GluR2-lacking AMPARs and another that does not.…”
Section: Discussionsupporting
confidence: 59%
“…It is possible that translocation of perisynaptic AMPARs and subunit switch occur very rapidly with pairing protocol and that these processes were already completed by the time PhTx433 was added (20). This scenario is consistent with more GluR2-containing AMPARs being present after LTP induction (42). An alternative scenario is that different induction protocols leads to two different forms of LTP, one that requires GluR2-lacking AMPARs and another that does not.…”
Section: Discussionsupporting
confidence: 59%
“…Similar results have been obtained at excitatory connections between cortical pyramidal neurons [35]. Other experimental data indicates that potentiation and depression events are switch-like transitions between binary conductance states, mediated by kinase and phosphotase pathways that are co-activated and competitive [36][37][38][39][40]. The kinetics of kinase and phosphotase activation also differ significantly, as LTP can be rapidly induced by appropriate patterns of activity while LTD requires prolonged stimulation [15,17,29].…”
Section: Introductionsupporting
confidence: 75%
“…It is also interesting to note that, due to the higher gain and shorter time constant governing kinase activation, transitions between low and high weight states induced by potentiating stimuli take consistently less time than transitions between high and low weight states induced by depressing stimuli (69±50s at ∆t=15ms and 108±55s at ∆t=-15ms for 5Hz Triplet pairing, for example), and each is on a similar timescale to that observed experimentally (80±70s for LTP and 183±126s for LTD in O'Connor, Wittenberg and Wang [37]; 38s for LTP in Bagal et al [39]). …”
Section: Induction Of Synaptic Plasticity By Spike-timing Stimulationsupporting
confidence: 58%
“…Previous studies that assess receptor movement biochemically or using epitope-tagged receptors have indicated that GluR1-containing AMPARs are delivered to extrasynaptic sites (31,32,34), and extrasynaptic AMPARs can be activated using exogenous agonists (47,48). However, our study defines the trafficking of native AMPARs around the perisynaptic region in response to activity-dependent LTP.…”
Section: Discussionmentioning
confidence: 57%